Study of ion cyclotron emission excited by tritium ions of fusion products via magnetoacoustic cyclotron instability theory in the EAST - Huapeng Zhang; Lunan Liu; Wei Zhang; Xuan Sun; Xinjun Zhang; Baolong Hao (Nuclear Fusion)
This study investigates the ion cyclotron emission (ICE) excited by tritium ions generated through deuterium‒deuterium fusion reactions in the Experimental Advanced Superconducting Tokamak (EAST). ICE is an electromagnetic instability driven by fast ions, and its excitation mechanism is primarily explained by magnetoacoustic cyclotron instability (MCI) theory, which describes energy transfer between fast ions and Alfvénic waves. Since ICE is closely related to the distribution of fast ions, the MCI growth rate is computed using linear theory based on the fast ion distribution calculated by TRANSP. Based on experimental parameters from EAST, we apply MCI theory to analyze the ICE growth rate and investigate the effects of key factors such as the propagation angle and the ratio of fast tritium ions to bulk deuterium plasma density. Experimental findings indicate that ICE excitation is at the fundamental frequency, simulations support that the propagation angle is approximately between 80° and 85°. At the fundamental frequency, the MCI growth rate increases with the propagation angle but decreases as the fast tritium ion density decreases. These results provide insights into the physics of ICE excitation and highlight its potential as the diagnostic tool for fast ions in future fusion reactors, including CFETR, DEMO, and ITER. Understanding ICE can help optimize fusion plasma performance and improve fast-ion confinement in next-generation magnetically confined fusion devices.